POLEMIK PEMBERIAN HARTA WARIS MELALUI WASIAT KEPADA ANAK ANGKAT - Habiburrahman, Habiburrahman (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2014)
This paper describes the polemic of the distribution of waris for foster child in the study of Islamic law and the laws and regulations in Indonesia. The distribution of estate to foster child was regulated in article 209 in the Compilation of Islamic Law (KHI). Thus, this is a signal that the influence of customary law and Western law had entered in KHI . Therefore, by this paper, Author would like to emphasize that the distribution of waris to the foster child by using the concept of wasiat wajibah in KHI is wrong. It is not based on the shari'ah (qath‘iy al-dilâlah), but rather based on logic of the law and humanitarian considerations, and it is zhanniy al-dilâlah. Thus, author sure that the distribution of waris by one third (1/3) of estate to the foster child by using the concept of wasiat wajibah is an erroneous ijtihad, cotradiction with the texts, and could be detrimental to the main heirs.